Post reform attitudes of New Zealand's senior public servants a follow up study. - Gregory, Robert (1995)
The articles provides and interprets the findings of an empirical approach designed to gain some insight into how the attitudes of senior public servants in Wellington have changed in few years since the reforms were implemented. The survey was concerned to gauge officials tolerance to pluralistic politics, their programmatic commitment, democratic sensibilities and identification with conventions the author says there might well be something of a trade-off between the desire to render public servants more proactive, on the one hand, and more accountable to their ministerial superiors, on the other
Keywords: Civil service reform - New Zealand; Civil service - New Zealand; Civil service